'You're thrown in the deep end': adult learner identity formation in higher education. Issue 12 (2nd December 2021) - Brunton, James; Buckley, Finian
ABSTRACT: For many adult learners transitioning into higher education is an intense experience that challenges their sense of themselves. This article reports on a study that examined the discourse of thirty-four undergraduate adult learners at the start and end of their first year in two Irish higher education institutions. The study focused on participants' evolving sense of who they were in the new educational context and how they incorporated this new adult learner identity into their existing identity portfolio, their overall sense of who they are. The key finding in this discursive psychology analysis of interview data was that participants engaged in two interrelated forms of identity work across their first year: constructing an identity formation narrative, about becoming adult learners; and ongoing, day-to-day identity management. The study illustrates how these adult learners experienced varying degrees of identity struggle, which had to be minimised if they were to maintain a consistent and coherent sense of themselves.